2007
DOI: 10.1002/polb.21169
|View full text |Cite
|
Sign up to set email alerts
|

Finite element method parametric study on scratch behavior of polymers

Abstract: Parametric studies were performed using finite element analysis (FEA) to learn how material and surface properties of polypropylene (PP) affect scratch behavior. Three-dimensional FEA modeling of scratching on a PP substrate with a spherical-tipped indenter is presented. Three different loading conditions, that is constant scratch depth, constant normal load, and linearly increasing normal load, are adopted for this parametric study. From the FEA findings, it is learned that Poisson's ratio has a negligible ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 14 publications
9
55
0
Order By: Relevance
“…Previous FEM results based on the traditional Coulomb friction failed to explain it and even displayed an opposite trend; with a growth of yield strength the scratch friction coefficient reduces (e.g., Ref. [8,10]). The reason was that with the growth of yield strength the deformation of surface material was suppressed, which led to a decrease of the surface deformation friction coefficient (SDFC) and caused a further drop in the SFC [13].…”
Section: Introductionmentioning
confidence: 94%
“…Previous FEM results based on the traditional Coulomb friction failed to explain it and even displayed an opposite trend; with a growth of yield strength the scratch friction coefficient reduces (e.g., Ref. [8,10]). The reason was that with the growth of yield strength the deformation of surface material was suppressed, which led to a decrease of the surface deformation friction coefficient (SDFC) and caused a further drop in the SFC [13].…”
Section: Introductionmentioning
confidence: 94%
“…11(b) than in Fig 11(a). Previous FEM results 12 showed that with a growth of the yield strength, scratch friction coefficient reduced. However, when plastic slippage is considered the scratch friction could increase with an increasing yield strength in our model, which is consistent with experimental observation for most metals.…”
Section: B Interpretation Of Experimentsmentioning
confidence: 99%
“…When indentation depth is on the micro-scale, coatings with crystalline materials due to GND have a strong size effect and classic elastoplasticity fails to describe it. This topic is out of range of previous finite element models [8][9][10][11][12][13][14][15][16] and this paper. However, if strain-gradient theories are applied to substitute the total system of equations in the Appendix, then compared with current results the extrusion and deformation of the coating will decrease and the area of the plastic slippage region will also reduce due to the additional hardening caused by GND under a micron indentation depth.…”
Section: Plastic Sliding During Indentationmentioning
confidence: 99%
See 2 more Smart Citations